Clinical Value of PPM1G Gene in Survival Prognosis and Immune Infiltration of Hepatocellular Carcinoma. (28th January 2022) - Xiao, Qingyu; Cheng, Zhen; Kuang, Wenbin; Wu, Haijun; Luo, Xi; Wang, Renling
Abstract : Objective . Liver cancer is one of the most common malignancies, but its prognosis is still poor. Exploring potential biomarkers is an important direction of tumor research. We intend to use bioinformatics methods to explore potential biomarkers related to survival and prognosis of HCC. Methods . The mRNA and protein expressions of PPM1G in liver cancer were analyzed by HPA, TIMER, and UALCAN databases, and the effects of PPM1G on the prognosis of liver cancer patients were explored by the GEPIA database. We also explored the correlation between PPM1G expression and liver cancer immune infiltration through the TIMER database and further explored the potential protein interaction network of PPM1G through the STRING database. Results . The mRNA and protein expression of PPM1G gene in hepatocellular carcinoma tissues was lower than that in normal adjacent tissues. Liver cancer patients with high expression of PPM1G have a better prognosis than those with low expression of PPM1G. The expression of PPM1G is positively or negatively correlated with different immune cells of liver cancer, such as CD4 + T lymphocytes, CD8+ T lymphocytes, B cells, macrophages, and neutrophils. Conclusion . The liver cancer patients with high expression of PPM1G have a good prognosis, and PPM1G gene may be a potential immunotherapy target and prognostic marker of liver cancer.